2006
DOI: 10.1258/095646206777689062
|View full text |Cite
|
Sign up to set email alerts
|

Distal sensory polyneuropathy in HIV-positive patients in the HAART era: an entity underestimated by clinical examination

Abstract: The aim of this study was to determine the prevalence of distal sensory polyneuropathy (DSP) in our HIV-positive patients under highly active antiretroviral therapy (HAART) and to investigate correlations with clinical, laboratory and demographic factors. One hundred consecutive HIV-positive patients underwent clinical and electrophysiological evaluation for DSP. Correlations with HIV stage, CD4 count, nadir CD4 count, viral load (VL), disease duration, age, sex and type of antiretrovirals were examined. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 0 publications
3
27
2
2
Order By: Relevance
“…Intriguingly, the symptoms of this syndrome are clinically indistinguishable from those of HIV-1-induced DSP, including a burning sensation in the hands and feet and hypersensitivity to pain (92,98,99). The fact that the two syndromes are usually seen in association with one another makes diagnosis more difficult.…”
Section: Chemokines Glia and Chronic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the symptoms of this syndrome are clinically indistinguishable from those of HIV-1-induced DSP, including a burning sensation in the hands and feet and hypersensitivity to pain (92,98,99). The fact that the two syndromes are usually seen in association with one another makes diagnosis more difficult.…”
Section: Chemokines Glia and Chronic Painmentioning
confidence: 99%
“…This has particular relevance for the present discussion because the cellular receptors for gp120, the HIV-1 coat protein, are the CXCR4 and CCR5 chemokine receptors. One example of an HIV-1-associated pain syndrome is distal symmetrical polyneuropathy (DSP), which affects as many as one third of all HIV-1-infected individuals (92). This painful sensory neuropathy frequently begins with paresthesias in the fingers and toes progressing over weeks to months, followed by the development of pain, often of a burning and lancinating nature, which can make walking very difficult.…”
Section: Chemokines Glia and Chronic Painmentioning
confidence: 99%
“…11 It is well established that DSP continues to be a prevalent neurologic complication associated with HIV infection in the HAART era, occurring in 36-62% of subjects infected with HIV. [1][2][3][4] Little is known about the incidence of DSP in the era of HAART. Lichtenstein et al 13 reported an incidence of five cases per 100 person-years from the HIV Outpatient Study (HOPS).…”
Section: Nakamoto Et Almentioning
confidence: 99%
“…1 Nonetheless, HIV-associated distal sensory neuropathy (DSP) continues to be a common neurologic complication seen in HIV-seropositive individuals. [2][3][4] Patients usually present with the gradual onset of distal sensory symptoms in the feet, including numbness, paresthesias, or painful dysesthesias. 5 The painful dysesthesias can be severe enough to limit activities of daily living.…”
mentioning
confidence: 99%
“…Most recently, it has been revealed that DSP affects 36% of patients under HAART. ddI was one of the important risk factors (Skopelitis et al 2006).…”
Section: Introductionmentioning
confidence: 99%